Diabetes-related knowledge, attitude and practices (KAP) of adult patients with type 2 diabetes mellitus in the Free State province, South Africa. Issue 4 (2nd October 2019) - Roux, Maretha le; Walsh, Corinna; Reid, Marianne; Raubenheimer, Jacques
Abstract : Introduction: Type 2 diabetes mellitus (T2DM) is a global health problem with high morbidity and mortality in patients who are mostly still economically active. The growing incidence and health implications for those affected make T2DM a major public health issue. Objectives: To compile a demographic, anthropometric and knowledge, attitude and practices (KAP) profile of adult patients with T2DM in the public health sector of the Free State province, South Africa. Design: A descriptive observational study was conducted. Setting: A total of 255 participants attending public health facilities in the Free State were interviewed. Outcome Measures: Questionnaires were completed in an interview to determine demographics and KAP. Anthropometric measurements were obtained by standard techniques. Results: The majority of the participants ( n = 222; 87.1%) were black women from urban areas, who were overweight and obese. The median age at diagnosis was 48 years (range 15–80 years), and 25 participants (9.8%) lacked formal schooling. In 212 participants (83.1%), a waist circumference above cut-off points was observed. Only half of the participants knew the normal range for blood glucose. Approximately 80% felt that they would be a different person if they did not have diabetes. Although 96.1% of participants were knowledgeable about the benefits of physical exercise, only 31.0% reported exercising on a daily basis. A statistically significant association was found between knowledge and attitudes, indicating that better knowledge about diabetes could be associated with a more positive attitude towards diabetes. Conclusion: Poor knowledge, a negative attitude and poor practices related to diabetes were observed in a very high percentage of participants, which may contribute to morbidity and mortality. The fact that knowledge was associated with attitude indicates that interventions aimed at improving knowledge could benefit patients in more than one way. Interventions to equip patients to successfully manage their condition are urgently required.